UPAYA PENGASUH PANTI ASUHAN DALAM MENGATASI KENAKALAN REMAJA DI YAYASAN PENYANTUNAN YATIM PIATU ACEH SEPAKAT DARUL AITAM - Ike Nurul Wahdanah; Kamalia Kamalia (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Juvenile delinquency is delinquency committed by children who are in their teens, starting from the age of 12-21 years by engaging in behavior that can cause harm and create unrest in society. The purpose of this research is to find out how efforts should be made in dealing with juvenile delinquency. The method used in this study is a qualitative method by obtaining data through observation, interviews and documentation. The results of this study explain that efforts to deal with juvenile delinquency by caregivers and also administrators at the Aceh Sepakat Darul Aitam Medan Orphanage Foundation can be carried out by instilling religious knowledge. Because the deeper the knowledge of religion is expected to be better one's behavior. The conclusion of this study is that parenting is a form of parenting without parents, which of course the orphanage caregivers take responsibility as biological parents. The efforts that have been made by the foundation are able to make the children in the foundation well-educated, so they don't commit juvenile delinquency which makes the local residents restless